The Challenges of Market Research in China - Lena Weick (Communications - Scientific letters of the University of Zilina, 2009)
This article analyses the challenges of current market research activities in China. A country that achieved remarkable economic development since the late 1970s and that is still continuing to grow.Firstly a picture of the market research industry in China is provided. Based on the history of market research, the leading companies and the most important types and aims of research are highlighted. The development of the market research industry in the framework of the Chinese market in general leads to challenges in primary and secondary research. Primary research in China is dominated by regional disparities, particularly in terms of language and culture. A continuous trend to urbanisation leads to a massive accumulation of individuals and enterprises in ‘mega cities’. Even so, the challenge of providing solid data quality seems to be still considerable. On the other hand, secondary data is still lacking in many ways. The availability is still sporadic and the quality remains inadequate. Furthermore the validity in general appears to be questionable.As discretionary income increases, the type and amount of products being consumed has changed significantly. Chinese customers are therefore confronted with a growing range of buying decisions. The rate of which the Chinese market is changing underlines the importance of research being up-to-date.